PENGARUH PENGGUNAAN MEDIA LOOSE PART TERHADAP KEMAMPUAN MOTORIK HALUS DAN KREATIVITAS ANAK KELOMPOK A DI TK CERDAS KABUPATEN BANYUWANGI TAHUN PELAJARAN 2022/2023 - Fatma, Patmawati; Waris, Waris; Kustiyowati, Kustiyowati (IAI Darussalam, 2023)
This study aims to determine the effect of using Loose Part media on fine motor skills and creativity of group A children in Smart Kindergarten, Banyuwangi Regency. The problem of not achieving fine motor skills and children's creativity optimally is the main background of this research. This study uses a quantitative descriptive approach, the type of research is pre-experimental design and the research pattern is one-group pretest-posttest. Collecting data using observation techniques, interviews and documentation. The research subjects were 17 children using purposive sampling method. Data analysis used the SPSS 25 statistical test. The results of the first hypothesis test had a significance value of 0.000, the results of the second hypothesis test had a significance value of 0.000 and the third hypothesis test had a significance value of 0.002, which means that the hypothesis is accepted. Conclusion: 1) There is an effect of using Loose Part media on children's fine motor skills, 2) There is an effect of using Loose Part media on children's Creativity. 3) There is an effect of using Loose Part media on fine motor skills and creativity of Group A children in Smart Kindergarten, Banyuwangi Regency.